A cross-sectional study of sleep, mood, well-being, motivations, and perceived support in Ukrainian veterans and active-duty military personnel with disability, and their supporters, preparing for a sporting event - Castle, Claire L.; Heinze, Nikki; Gomes, Renata S. M. (Frontiers in Psychology, 2023)
Purpose The benefits of sports and exercise to the lives and rehabilitative journeys of military veterans with disabilities is increasingly well-documented but veteran sporting events remain underexplored. Addressing this topic, the current article seeks to provide insight into the health and well-being of Team Ukraine during a 5-week preparatory camp in the UK before attendance at the 2022 Warrior Games. Materials and methods Two surveys were run, one towards the beginning and one towards the end of the camp. Eighteen of the 55 veterans and serving personnel (with disability), support staff, and family members in attendance responded to both surveys. Data on sleep, mood, and competition-related emotions, motivations for participation and perceived support were gathered. Data were analysed descriptively, and sleep, mood, and competition-related emotion responses were categorised to explore improvements, maintenance, or worsening in these areas. Results and conclusions Sleep, mood, and competition-related emotions were relatively stable, although sleep duration was low, and there were some increases in daytime dysfunction, anxiety, nervousness, and feeling tense. Family was the most important source of support and representation of one’s country and raising awareness of Ukraine’s circumstances were the most important motivational factors. Findings offer insight into not only the health and well-being experiences associated with participation in this disabled veteran sporting event, but also the important role played by this event in meeting collective goals relating to this unique time in Ukraine’s history.